Self-talk and emotions in tennis players during competitive matches. Issue 3 (4th May 2022) - Fritsch, Julian; Jekauc, Darko; Elsborg, Peter; Latinjak, Alexander Tibor; Reichert, Markus; Hatzigeorgiadis, Antonis
Abstract: A theory-driven classification recently introduced to sport psychology distinguishes between goal-directed self-talk as a controlled type of self-talk, and spontaneous self-talk as an uncontrolled type of self-talk. Based on this classification, the aim of this study was to explore the relationship between self-talk and emotions. To this end, twenty competitive tennis matches were video-recorded. Shortly after the match, the players were confronted with situations from the match and asked to rate the intensity of their emotions experienced, the intensity of their outward emotional reactions, and to report on their self-talk. Multilevel fixed and random effect models showed that the intensity of emotions experienced (fixed model: β = −1.40; p < .01; random model: β = −1.40; p < .01) and outward emotional reactions (fixed model: β = −0.79; p < .01; random model: β = −0.76; p < .05) were lower in instances where players reported solely goal-directed self-talk than in instances where players reported solely spontaneous self-talk. Moreover, in the fixed model, the intensity of emotions experienced was also lower in instances where players reported goal-directed self-talk in conjunction with spontaneous self-talk, compared to instances where players reported solely spontaneous self-talk ( β = −0.46; p < .01). Finally, exploratory analyses suggest that these effects are mostly true for negative emotions rather than positive ones. Overall, the findings support the relevance of dual-process self-talk approaches. These findings encourage players to gain awareness about their emotions through spontaneous self-talk, while they can use goal-directed self-talk for emotion regulation. Lay summary: During a match, most tennis players talk a lot to themselves. This study shows that their self-talk is related to (a) the emotions they experience and (b) the emotions they show to the outside. Specifically, a goal-oriented type of self-talk is related to less intense emotions. Implications for practice: Players can gain awareness about their emotional states through spontaneous self-talk. Players can use goal-directed self-talk to proactively and reactively regulate emotions. Video-assisted recall can be helpful to assess and learn to deal with challenging psychological states during sport competitions.